An audit of caesarean sections performed for suspected fetal distress at Mowbray Maternity Hospital in 2018 - Moreri-Ntshabele, Badani (Department of Obstetrics and Gynaecology, 2023)
Background The cardiotocograph (CTG) is used for fetal monitoring antenatally and in labour, to detect potential fetal hypoxia and thus prevent perinatal morbidity and mortality. An abnormal CTG influences decisions clinicians make in terms of timing and mode of delivery, as the type of abnormality may warrant immediate delivery by caesarean section (CS). However caesarean section rates are increasing worldwide and in South Africa, and ‘fetal distress' is one of the common indications. The increased CS rate also increases the risk of maternal morbidity and mortality. At Mowbray Maternity Hospital, weekly review meetings show that ‘pathological CTG' and ‘non reassuring CTG' accounted for the majority of emergency CS. Therefore, this study was undertaken to see if ‘fetal distress' is being over-diagnosed leading to unnecessary CS, or to affirm that the CS are correctly indicated for this diagnosis. Hence an investigation of caesarean sections done for ‘fetal distress in 2018 was performed in order to audit emergency CS performed at MMH for abnormal CTG tracings. Methods A retrospective observational study with a comparative component was performed. The PASS 2022 software was used to calculate the sample size. The calculation was made for proportions of agreement using a kappa statistic which was calculated to be 114 cases. The study population was derived from the institutional theatre register, in which patients, who had an emergency CS for an abnormal CTG or ‘fetal distress', between 01 January 2018 and 31 March 2018 were included. The CTGs were interpreted by the two obstetric specialistts (experts) and this was compared with the original interpretation made by the attending doctor. In addition, the independent experts assessed the appropriateness of the decision for CS. Data was also obtained on co-existing obstetric conditions, and perinatal and maternal outcomes. Ethics approval for the study was attained from the University of Cape Town Human Research Ethics Committee (UCT HREC) and facility approval from MMH. Results Ninety cases were identified from the study period and analysed. The attending doctor assessed 22 (24.4%) CTGs as suspicious and 68 (75.6%) as pathological, whereas the experts assessed 7 (7.8%) as normal, 22 (24.4%) as suspicious and 61 (67.8%) as pathological. There was overall agreement in CTG interpretation between the experts and the attendant doctor for 61 cases (67.8%). The reliability of this agreement was measured using Cohen's Kappa and was 0.247 (CI 0.153-0.341). This is a ‘fair' level of agreement. A further analysis showed that there was a higher proportion of agreement with pathological CTGs and a lower proportion of agreement for suspicious CTGs which accounted for 52 (57.8%) and 9 (10%) cases, respectively. A review of the medical records showed that 69 (77%) of patients had one or more co-existing obstetric condition such as prolonged pregnancy, hypertensive disorders, prolonged rupture of membranes and meconium-stained liquor etc. When considering these obstetric factors as well as the CTG, the experts assessed 16 women (17.8%) to have had unnecessary caesarean sections. In terms of neonatal outcomes, the mean five-minute APGAR was 8, and only 3 babies had a five-minute APGAR which was less than 7. Twelve babies (13.3%) babies were admitted to the neonatal unit and of those, 4 (4.4%) were admitted for low Apgar scores. The commonest maternal complication was PPH which affected 8.9% of the patients. Conclusion The inter-observer agreement in CTG interpretation at MMH was fair, which is comparable to other studies done in the world, with agreement on the indication for CS of 82.2%. The agreement in CTG interpretation was high with pathological CTGs and poor with suspicious CTGs. A second opinion for CS for abnormal CTG may reduce the number of unnecessary CS especially for suspicious CTGs. A normal CTG tends to affirm good fetal wellbeing, however an abnormal CTG does not always mean that there is fetal compromise, therefore the clinical condition must be evaluated together with the CTG to make an appropriate decision with regards to timing and mode of delivery.